2023
DOI: 10.1186/s12987-023-00425-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct association with the vascular basement membrane is a frequent feature of myelinating oligodendrocytes in the neocortex

Abstract: Background Oligodendrocyte lineage cells interact with the vasculature in the gray matter. Physical and functional interactions between blood vessels and oligodendrocyte precursor cells play an essential role in both the developing and adult brain. Oligodendrocyte precursor cells have been shown to migrate along the vasculature and subsequently detach from it during their differentiation to oligodendrocytes. However, the association of mature oligodendrocytes with blood vessels has been noted s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…It was recently shown that mature oligodendrocytes in gray matter directly associate with the vascular BM. 43 In this report, ∼17% of oligodendrocytes mainly contact with capillaries, but not with arterioles or venules, in the mouse cerebral cortex, hippocampus, and cerebellum. In this study, we did not observe the MBP oligodendrocyte marker signal on the isolated blood vessels, but our mass spectrometry analysis showed that oligodendrocyte marker proteins, such as Mag, Mog, and Cntn2, were detected in the purified PV-AEF fraction.…”
Section: Discussionmentioning
confidence: 54%
“…It was recently shown that mature oligodendrocytes in gray matter directly associate with the vascular BM. 43 In this report, ∼17% of oligodendrocytes mainly contact with capillaries, but not with arterioles or venules, in the mouse cerebral cortex, hippocampus, and cerebellum. In this study, we did not observe the MBP oligodendrocyte marker signal on the isolated blood vessels, but our mass spectrometry analysis showed that oligodendrocyte marker proteins, such as Mag, Mog, and Cntn2, were detected in the purified PV-AEF fraction.…”
Section: Discussionmentioning
confidence: 54%
“…We also note recent reports by Yang et al 4 on the AD-relevant activity of CR1 within perivascular macrophages (PVM). Given complex reciprocal interactions between oligodendrocytes and the neurovascular unit 66 , 67 , simultaneous evaluation of CR1 and AD GWAS loci in PVM and oligodendrocytes may illuminate a shared mechanism that could explain the observed CNS as well as hematological effects in a parsimonious manner. Further study of whether peripheral CR1 levels are associated with rs679515 in an AD-specific manner may also be an informative direction for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We also note recent reports by Yang et al 58 on AD-relevant activity of CR1 within perivascular macrophages (PVM). Given complex reciprocal interactions between oligodendrocytes and the neurovascular unit 59,60 , simultaneous evaluation of CR1 and AD GWAS loci in PVM and oligodendrocytes may illuminate a shared mechanism that could explain the observed CNS as well as hematological effects in a parsimonious manner. Further investigation of whether rs679515 is associated with alterations of peripheral CR1 may also represent a fruitful path for future study.…”
Section: Discussionmentioning
confidence: 99%